Linking in situ crystallisation and magma replenishment in the Rum Layered Intrusion, NW Scotland - Hepworth, Luke Nathan (2018)
Layered intrusions offer an exceptional opportunity to study magmatic processes operating in the upper crust, including the concentration of world class precious-metal deposits. Despite the importance for understanding igneous processes and mineral resources, the fundamental construction mechanism of these intrusions is not well understood. The Rum Layered Suite (RLS) in NW Scotland represents an archetypal open-system layered intrusion that formed as part of the North Atlantic Igneous Province ~60 Ma. The peridotite cumulates within the RLS are poorly studied, where formation is typically attributed to the early stages of batch-fractionation from picritic and basaltic magma. This study focuses on the peridotite cumulates from Unit 10 in the Eastern Layered Intrusion (ELI) and Western Layered Intrusion (WLI). The cumulates contain abundant harrisite, an unusual skeletal-olivine bearing peridotite that crystallised in situ. Harrisite layers are used to represent picrite sills, with features of harrisite in Unit 10 and WLI, inconsistent with processes occurring on the magma chamber floor, also highlighting multiple replenishment events. The unusual olivine morphology in harrisites is controlled by the crystal mush temperature on intrusion, enhancing undercooling (i.e., chilling). Picrite emplacement caused a reaction with intercumulus plagioclase, forming Cr-spinel seams in situ alongside harrisite. The seam formed in discrete intra-mush melt channels where spinel chemistry, texture, and precious-metal enrichment is controlled by melt flux. Lateral magma intrusion and melt migration was facilitated by slow gravitational collapse of the crystal mush, producing planar shear zones and hot tears in a high-crystallinity framework. Repeated sill emplacement caused widespread dissolution to pre-existing cumulate and recrystallisation of primary mineralogy in situ by infiltrating melt. The evidence presented here is used to argue against traditional magma chamber models of layered intrusion growth, where the RLS instead ...